2007
DOI: 10.1021/ja070137q
|View full text |Cite
|
Sign up to set email alerts
|

Stern−Gerlach Experiments of One-Dimensional Metal−Benzene Sandwich Clusters:  Mn(C6H6)m (M = Al, Sc, Ti, and V)

Abstract: A molecular beam of multilayer metal-benzene organometallic clusters Mn(C6H6)m (M = Al, Sc, Ti, and V) was produced by a laser vaporization synthesis method, and their magnetic deflections were measured. Multidecker sandwich clusters of transition-metal atoms and benzene Scn(C6H6)n+1 (n = 1, 2) and Vn(C6H6)n+1 (n = 1-4) possess magnetic moments that increase monotonously with n. The magnetic moments of Al(C6H6), Scn(C6H6)n+1, and Vn(C6H6)n+1 are smaller than that of their spin-only values as a result of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 67 publications
(87 reference statements)
11
140
0
Order By: Relevance
“…The neutral analogs have been recently studied by magnetic deflection. 8 The stoichiometries of these clusters led to the proposal of a structure of sandwiches with the M atoms intercalated between benzene units. The magnetism observed in some of them was associated to the spin-coupling along the axis of the sandwich.…”
Section: -17͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The neutral analogs have been recently studied by magnetic deflection. 8 The stoichiometries of these clusters led to the proposal of a structure of sandwiches with the M atoms intercalated between benzene units. The magnetism observed in some of them was associated to the spin-coupling along the axis of the sandwich.…”
Section: -17͒mentioning
confidence: 99%
“…The choice of Ti, V, and Cr is based on: ͑i͒ the experimental evidence that the tendency to form multidecker sandwiches is stronger for the early than for the late transition metals; low-lying electronic states that are coupled to the groundstate through allowed optical transitions; 24 and ͑iii͒ the possibility of comparing the absorption properties of magnetic ͑V n Bz n+1 ͒ and nonmagnetic ͑Ti n Bz n+1 and Cr n Bz n+1 ͒ systems. 8,10 Our aim is to study the changes in the electronic properties, as reflected in the photoabsorption spectrum, as the sandwich size and the metallic element are varied. We find that the optical properties of the sandwiches can be tuned by varying the number of units.…”
Section: -17͒mentioning
confidence: 99%
“…In particular, a wide variety of experimental and theoretical efforts have been devoted to the characterization for a multidecker sandwich structure, 19,66,67,96103 because it has been found that M n (Bz) n+1 clusters possess unique size-dependent ferromagnetic properties originating from their one-dimensional structures, where V n (Bz) n+1 clusters exhibit the increase in their magnetic moments monotonically with the cluster size. 28,29 Hence, it is anticipated that they become one of the most promising candidates as building blocks in nanoscale spintronic devices. In order to utilize attractive functional clusters as building blocks in functional materials, however, matrix-isolation at temperatures at or above room temperature is highly desired.…”
Section: The Role Of Cage Aromaticity Of MX 16mentioning
confidence: 99%
“…Considerable experimental and theoretical studies have revealed that the characteristics of the transition metalBz clusters, including geometry, 19,66,97 stability, 67,99 optical 98 and magnetic 28,29,100,101 properties, are highly dependent on the nature of the transition metals in the clusters, in particular, the change in the number of 3d electrons. Figure 14 shows the IRAS spectra in the 6501550 cm ¹1 region after the soft-landing of M(Bz) 2 cation clusters (M = Ti, V, and Cr) onto the n-octadecanethiol SAM (C 18 -SAM) substrates using our soft-landing apparatus as shown in Figure 3.…”
Section: Soft-landing Isolation Of Transition Metalbenzene Clustersmentioning
confidence: 99%
See 1 more Smart Citation